Pelatihan Penulisan Penelitian Tindakan Kelas Untuk Guru-Guru Sekolah Dasar di Kecamatan Slahung Kabupaten Ponorogo - Saputro, Agung Nasrulloh (Lumbung Pare Cendekia, 2024)
The poor ability of elementary school teachers in writing classroom action research is the main driver of this commitment. The purpose of this project is to teach educators how to write classroom action research projects. Training and seminar techniques are used in this service approach. The training location is at SDN 01 Slahung Ponorogo. Teachers can compile classroom action research appropriately because of this commitment. This commitment is intended as a guide for educators who want to improve their ability to write classroom action research in the classroom. Primary school teachers now have a better understanding and proficiency in writing PTK and its output.